Factors that makes up profitable customer loyalty toward the organizations / Nurul Huda Mohamad - Mohamad, Nurul Huda (Faculty of Business and Management, 2009)
The research has been conducted at Apex Communications Sdn Bhd at Jalan P.Ramlee, Kuala Lumpur. This research is about a study on factors that makes unprofitable customer loyalty toward the organization. This research is conducted in order to know the customer loyalty toward the organizations because we have three factors, which is relationship strength, perceived alternatives and critical episodes. The objectives of this research are to determine the level of customer loyalty and its factors toward Apex Communications Sdn Bhd. Based on the study, customer loyalty is important to any organization in term of enhancing their profit and to retain its current customers. In order to sustain their competitiveness in the marketplace, each firm needs to provide the excellent services towards their customers. If the firms failed to maintain and enhanced their services, it is impossible for them to achieve their targets. Further, this study also is more emphasizing regarding to the organizations need improvement to maintain their relationship with customers. It is because that has some factors, the organization do not practice entirely to ensure that their relationship with customer becomes more enjoyable and efficient but only several factors that the organizations apply to fulfill customer needs and wants the result of this research will show the importance factors of customer loyalty, which are, contribute to the loyalty. In addition, the article concludes with a discussion of the research to improved understanding of the factor that makes up profitable customer loyalty toward the organization.